Vernacular names of toxic plants used as medicine in the central Middle Atlas - Morocco - Najem, Mariame; Nassiri, laila; Ibijbijen, Jamal (Ethnobotany Research and Applications, 2020)
Background: The present study is part of investigations dedicated to the valorization of the medicinal flora and traditional knowledge of the moroccan central Middle Atlas. It focused on the vernacular names of toxic plants used for medicinal purposes in that region. Methods: Through ethnobotanical investigations carried out in the region with herbalists, druggists and traditional practitioners, followed by floristic prospecting in the field, toxic plants used for medicinal purposes in the central Middle Atlas were identified. Their local vernacular names were collected from the surveyed phytotherapists. Then, several scientific publications and books were analysed in order to specify whether the vernacular names are specific to the central Middle Atlas region or are common in Morocco, or even in the Maghreb. Results: In the study area, 83 plants species used for medicinal purposes, belonging to 75 genera and spread over 39 families have been declared toxic; of these 83 plant species, 52 each have only one name in Arabic or Berber dialect, 7 of which are used exclusively in the central Middle Atlas. The 31 other plants are each known by at least two vernaculars, 6 of which are specific to the central Middle Atlas. In Morocco as well as in the other Maghreb countries, most of the inventoried plant species have a multitude of vernacular names, some of which date back hundreds of years. On the one hand, the meaning of these vernacular names alludes to the common use of the plant, one of its morphological particularities, a pigment, a myth or a biotope; on the other hand, it reflects the socio-cultural heterogeneity, firstly in the study area, but especially throughout the country and North Africa. Conclusions: This study made it possible to draw up a non-exhaustive list of vernacular names of toxic plants used as medicine in the central Middle Atlas whose diversity indicates the socio-cultural diversity of the local population and his knowledge of the characteristics and properties of plant species. Key words: Ethnobotany, Toxic plants, Vernacular Names, Diversity, Central Middle Atlas, Morocco, Maghreb